Analisis Faktor Internal Dan Eksternal Dengan Antenatal Care (ANC) K4 Di Wilayah Kerja Puskesmas Teluk Dalam Kota Banjarmasin Tahun 2017 - Abdullah Abdullah; Norfai Norfai (Jurnal Kesehatan Indonesia, 2018)
Antenatal Care is a periodic health service during pregnancy of mothers organized by health professionals such as obstetricians, midwives, general practitioners, midwives and nurses to pregnant women and the fetus they have to ensure that pregnant women can be running pregnancy, parturition, puerperium well and survived and have healthy baby. The coverage of ANC K4 in Teluk Dalam Public Health Center has been decreasing percentage from 2015 by 96% to 85% in 2016. This study aims to know and analyze the relationship of mother's age, education, parity, knowledge, pregnant mother's class visit and husband support with Antenatal Care (ANC) K4 in working area in Banjarmasin Teluk Dalam Public Health Center in 2017. This research is an analytical survey with cross sectional approach. The sample amount is 84 respondents by purposive sampling. Data were collected using questionnaires distributed directly to respondents. Data were analyzed using univariate statistic and bivariate of Che Square test with alternative test of Fisher Exact test using computer program with significance value (α) 0,05. The result of this research stated that respondents who do Antenatal Care according to minimum standard Antenatal Care (ANC) K4 is 53,6% while those who do not conduct Antenatal Care according to minimum standard Antenatal Care (ANC) K4 equal to 46,4%. Variables that were statistically significantly related to Antenatal Care (ANC) K4(p-value ≤ 0.05) were age, knowledge, maternal class visits and husband support.